An Objective Approach to Identifying Diagnostic Expertise Among Power System Controllers. (February 2013) - Loveday, Thomas; Wiggins, Mark W.; Harris, Jemma M.; O'Hare, David; Smith, Neil
Objective: The present study investigated whether performance across a range of cue-based cognitive tasks differentiated the diagnostic performance of power control operators into three distinct groups, characteristic of novice, competence, and expertise. Background: Despite its increasing importance in the contemporary workplace, there is little understanding of the cognitive processes that distinguish novice, competent, and expert performance in the context of remote diagnosis. However, recent evidence suggests that cue acquisition and utilization may represent a mechanism by which the transition from novice to expertise occurs. Method: The study involved the application of four distinct cue-based tasks within the context of power system control. A total of 65 controllers, encompassing a range of industry experience, completed the tasks as part of an in-service training program. Results: Using a cluster analysis, it was possible to extract three distinct groups of operators on the basis of their performance in the cue-based tasks, and these groups corresponded to differences in diagnostic performance. Conclusion: The results indicate assessments of the capacity to extract and utilize cues were able to distinguish expert from competent practitioners in the context of power control. Application: Assessments of the capacity to extract and utilize cues may be used in the future to distinguish expert from nonexpert practitioners, particularly in the context of remote diagnosis.